2018
DOI: 10.1021/acsnano.8b03712
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Internal Atomic Charge Density Distributions in Real Space

Abstract: Probing the charge density distributions in materials at atomic scale remains an extremely demanding task, particularly in real space. However, recent advances in differential phase contrast-scanning transmission electron microscopy (DPC-STEM) bring this possibility closer by directly visualizing the atomic electric field. DPC-STEM at atomic resolutions measures how a sub-angstrom electron probe passing through a material is affected by the atomic electric field, the field between the nucleus and the surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…According to Gauss's law, the charge-density map can be obtained by calculating the differential of the electric field map 23,24,[59][60][61][62] . Then, according to the relation between the electric field (E) and charge density (ρ) 49,51 ρ…”
Section: Discussionmentioning
confidence: 99%
“…According to Gauss's law, the charge-density map can be obtained by calculating the differential of the electric field map 23,24,[59][60][61][62] . Then, according to the relation between the electric field (E) and charge density (ρ) 49,51 ρ…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by detailed model simulations that this negative charge is not an artifact due to dynamical electron scattering effects. 22) It can be concluded that the negative charge contrast observed experimentally is the visualization of the electron cloud around the atomic nucleus in real space. Thus, the charge density distribution even inside atoms can be imaged by atomic-resolution STEM.…”
Section: Towards Real-space Imaging Of Local Charge Densitymentioning
confidence: 97%
“…Figure 7 shows the result of the observation of the charge density distribution by atomic-resolution DPC STEM with a GaN single crystal. 22) Figure 7(a) shows the simultaneous ADF, 7(b) shows the electric field vector color map, and 7(c) shows the charge density map converted from 7(b). While only the Ga atom columns can be observed in the ADF, both the Ga and N atom columns are clearly imaged in the electric field map.…”
Section: Towards Real-space Imaging Of Local Charge Densitymentioning
confidence: 99%
“…In this context, understanding the structure of LiMn2O4 is of paramount importance to be able to maximize its storage capabilities, control the safety issues and reduce the capacity loss. Recent advances in scanning transmission electron microscopy (STEM) allow us to observe not only the structure of the materials at atomic level, but also to obtain images proportional to the projected potential [2], the projected electric field [3] and the projected charge distribution [4], by using differential phase contrast technique (DPC). Thus, in this work we use DPC to determine the Li, Mn and O atoms positions, thus providing a novel insight into the structure of LiMn2O4.…”
mentioning
confidence: 99%
“…Simultaneously, annular dark field (ADF), annular bright field (ABF) and DPC images were obtain from pristine LiMn2O4 nanoparticles. A segmented annular detector was used to image the in-plane displacement of the transmitted electrons, which is proportional to the projected electric field, while the images proportional to the potential and charge distribution were calculated accordingly to [2,4]. Our results clearly show local regions depleted in Li and the existence of manganese atoms in tetrahedral sites occupying a typical Li atom position, or occupying a free octahedral site in the same column, in agreement with the Mn disproportionation reaction reported for such compound.…”
mentioning
confidence: 99%